ANALISIS PERILAKU PENGGUNA TEKNOLOGI ATAS PENERIMAAN LAYANAN E-SAMSAT MENGGUNAKAN MODEL TAM DAN TPB (Studi Kasus Pada SAMSAT Wilayah Kabupaten Subang) - Nurhamidah Nurhamidah; Asep Kurniawan; Indah Umiyati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2018)
This study aims to examine and analyze the model of technology user behavior on the acceptance of an information system on e-samsat Application system. With sample number 100 respondents with sampling using incidental sampling technique. Hypothesis testing used is Structural Equation Modeling (SEM). Based on the results say that Perceived Ease of Use variable has a positive and significant effect on Perceived of Usefulness and Trust. The Perceived of Usefulness variable has a positive and significant effect on Attitude and Behavior Intention. Trust variables have a positive and significant influence on Perceived of Usefulness, Perceived Behavior Control, Attitude, Perceived of Risk and Subjective Norm. Perceived Behavior Control and Attitude variables have positive and significant effect on Behavior Intention.